Serum levels of brain-derived neurotrophic factor in alcohol-dependent patients receiving high-dose baclofen. (30th June 2016) - Geisel, Olga; Hellweg, Rainer; Müller, Christian A.
Abstract: The neurotrophin brain-derived neurotrophic factor (BDNF) has been suggested to be involved in the development and maintenance of addictive and other psychiatric disorders. Also, interactions of γ-aminobutyric acid (GABA)-ergic compounds and BDNF have been reported. The objective of this study was to investigate serum levels of BDNF over time in alcohol-dependent patients receiving individually titrated high-dose treatment (30–270 mg/d) with the GABA-B receptor agonist baclofen or placebo for up to 20 weeks. Serum levels of BDNF were measured in patients of the baclofen/placebo group at baseline (t0), 2 weeks after reaching individual high-dose of baclofen/placebo treatment (t1) and after termination of study medication (t2) in comparison to carefully matched healthy controls. No significant differences in serum levels of BDNF between the baclofen and the placebo group or healthy controls were found at t0, t1, or at t2. Based on these findings, it seems unlikely that baclofen exerts a direct effect on serum levels of BDNF in alcohol-dependent patients. Future studies are needed to further explore the mechanism of action of baclofen and its possible relationship to BDNF in alcohol use disorders. Highlights: A RCT investigating the effects of high-dose baclofen on serum levels of BDNF in alcohol-dependent patients. Measurement of serum levels of BDNF at baseline, during high-dose treatment and after termination of study medication. No significant differences in serum levels of BDNF between the baclofen and the placebo group or healthy controls.